2018
DOI: 10.14791/btrt.2018.6.e13
|View full text |Cite
|
Sign up to set email alerts
|

Current Radiopharmaceuticals for Positron Emission Tomography of Brain Tumors

Abstract: Brain tumors represent a diverse spectrum of histology, biology, prognosis, and treatment options. Although MRI remains the gold standard for morphological tumor characterization, positron emission tomography (PET) can play a critical role in evaluating disease status. This article focuses on the use of PET with radiolabeled glucose and amino acid analogs to aid in the diagnosis of tumors and differentiate between recurrent tumors and radiation necrosis. The most widely used tracer is 18F-fluorodeoxyglucose (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 74 publications
0
26
0
4
Order By: Relevance
“…At the time of writing, is still unclear which PET tracer is superior in distinguishing tumor recurrence from RN [65]. One of the most interesting studies in this sense is one by Tomura et al, which demonstrated that 11 C-MET PET was superior to 18 F-FDG-PET in differentiating RN from tumor recurrence, mainly in patients that already underwent gamma knife radiosurgery.…”
Section: Discussionmentioning
confidence: 99%
“…At the time of writing, is still unclear which PET tracer is superior in distinguishing tumor recurrence from RN [65]. One of the most interesting studies in this sense is one by Tomura et al, which demonstrated that 11 C-MET PET was superior to 18 F-FDG-PET in differentiating RN from tumor recurrence, mainly in patients that already underwent gamma knife radiosurgery.…”
Section: Discussionmentioning
confidence: 99%
“…On this basis, 2-deoxy-2-[fluorine-18]fluoro-D-glucose ([ 18 F]FDG) is the most used radiotracer in cancer; indeed, most cancers display increased glucose uptake and phosphorylation and there is a tight correlation between [ 18 F]FDG uptake and cell viability [ 217 ]. Unfortunately, the brain tumour imaging represents a unique challenge because of the high background uptake due to normal grey matter which makes it very difficult to efficiently visualize with [ 18 F]FDG PET [ 274 ].…”
Section: In Vivo Imaging For the Study Of Gbm Heterogeneity And MImentioning
confidence: 99%
“…Apart from the usual qualitative uptake parameters, various novel parameters such as shape and uptake heterogeneity may provide additional information on the biologic profile of tumor. 80 Furthermore, with the introduction of theranostics, which uses the same radiopharmaceuticals for diagnosis and therapy of tumors, better patient management is anticipated. It is achieved by exchanging the radionuclide, that is, short-lived positron emitter 68 Ga used for PET with the longer-lived b -emitters such as yttrium-90 or lutetium-177 for therapy purposes.…”
Section: Challenges and Future Directionsmentioning
confidence: 99%